Discrimination of alcoholic (khamar) and non-alcoholic beverages using an electronic nose - Arshad, Syariena; Che Man, Yaakob (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Nowadays khamar abuse had become a social problem among Muslims. Islamic religion prohibited khamar consumption because of the effect that khamar has on the body and behavior.Some Islamic country had restricted the consumption and distribution of khamar for Muslims and underage citizens. Thus it is essential to establish a method that can detect and discriminate khamar from non-alcoholic beverages. This study demonstrates the usage of electronic nose (zNoseTM) for khamar and non-alcoholic beverages discrimination. This device had the advantages of fast and in situ measurement compared to conventional devices which come with bulky equipment and were time consuming. The principal detection of aroma compound was based on gas chromatogram and detected by the surface acoustic wave (SAW) sensor. Four different types of khamar and three different types of non-alcoholic beverages were analyzed and categorized using the principal component analysis (PCA). The PCA analysis revealed that 84% of the total variance was described by PC 1 and PC 2.